The Guardian of the Integral Vision of Islamic Practice: The Naqshabandi Sufi Order in Indonesia - Umam, Saiful (Studia Islamika, 2006)
This article, particularly the discussion on pesantrens, shows that only tariqa which supports fiqh is acceptable to and practiced by kiai and santri. This contradicts Trimingham's argument that Indonesians prefer heterodox mysticism. Comparing Muslims in Africa and Indonesia, Trimingham argues that Muslims in Indonesia place more emphasis on "thinking than upon acting" and therefore "speculative mysticism" is prevalent in this countryDOI: 10.15408/sdi.v13i2.568